Pengaruh Likuiditas dan Leverage Terhadap Nilai Perusahaan Dengan Profitabilitas Sebagai Variabel Moderasi (Perusahaan Subsektor Logam dan Sejenisnya Periode 2019-2023) - Pulukadang, Vetty Damayanti; Monoarfa, Moh. Agus Salim; Fransissca, Dungga , Meriyana (Paradoks : Jurnal Ilmu Ekonomi, 2024)
This study aims to examine the influence of liquidity and leverage on firm value with profitability as a moderating variable (a case study on metal and similar subsektor companies listed on the Indonesia Stock Exchange for the period of 2019-2023). Sthhe study uses purposive sampling, resulting in a total sample of 14 metal companies and similar companies. The data collection relies on secondary data, specifically financial reports published by the Indonesia Stock Exchange (IDX). The anlysis is conducted using The Partial Least Squares (PLS) method with the assistance of SmartPLS 3.2.9 software. The research finding and data analysis indicate that liquidity, leverage, and profitability partially influence firm value, In addition, profitability moderates the relationship between liquidity and firm value, but does not moderate the relationship between leverage and firm value.